Pengaruh Kualitas Produk Kripik Wahyu Terhadap Kepuasan Konsumen (Studi Kasus Toko Golden Hill Luwuk): The Effect of Wahyu Kripik Product Quality on Consumer Satisfaction (Case Study of Golden Hill Luwuk Store) - Sarlin Lahuma; Arpan Kurubit; Andrie Firmansyah (Jurnal Ilmiah Produktif, 2020)
This study aims to determine whether the Quality of Wahyu Kripik Products affects Consumer Satisfaction (a case study of purchasing at Golden Hill Luwuk). The analytical method used in this study is simple linear regression analysis using 100 samples taken using the accidental sampling technique. Based on the results of research and testing, it is concluded that the variable quality of Wahyu's products affects consumer satisfaction (a case study of purchasing at Golden Hill Luwuk). Meanwhile, the close relationship between product quality and consumer satisfaction (a case study of purchasing at Golden Hill Luwuk) is in a low category, and the contribution of product quality variables to consumer satisfaction variables is 10.5%, while the remaining 89.5% is caused by factors other than not investigated.